Superalkali Coated Rydberg Molecules - Tkachenko, Nikolay V.; Rublev, Pavel; Boldyrev, Alexander I.; Lehn, Jean-Marie (Frontiers in Chemistry, 2022)
A series of complexes of Na, K, NH4, and H3O with [bpy.bpy.bpy]cryptand, [2.2.2]cryptand, and spherical cryptand were investigated via DFT and ab initio methods. We found that by coating Rydberg molecules with the “organic skin” one could further decrease their ionization potential energy, reaching the values of 1.5 eV and a new low record of 1.3 eV. The neutral cryptand complexes in this sense possess a weakly bounded electron and may be considered as very strong reducing agents. Moreover, the presence of an organic cage increases the thermodynamic stability of Rydberg molecules making them stable toward the proton detachment.